Effect of Dissemination of Evidence in Reducing Injuries from Falls - Tinetti, Mary E; Baker, Dorothy I; King, Mary; Gottschalk, Margaret; Murphy, Terrence E; Acampora, Denise; Carlin, Bradley P; Leo-Summers, Linda; Allore, Heather G (The New England journal of medicine, 2008)
Effective strategies to prevent falls among elderly persons have been identified but are underutilized. In this comparison of a region of Connecticut in which persons were exposed to interventions to prevent falls and a region without such exposure, the interventions were associated with a 9% reduction in serious injuries from falls. These findings suggest that the dissemination of information about fall prevention may reduce numbers of falls and serious injuries. In this comparison of a region of Connecticut in which persons were exposed to interventions to prevent falls and a region without such exposure, the interventions were associated with a 9% reduction in serious injuries from falls. Fall-related injuries are among the most common, morbid, and expensive health conditions involving older adults. 1 – 5 Falls account for 10% of emergency department visits and 6% of hospitalizations among persons over the age of 65 years and are major determinants of functional decline, nursing-home placement, and restricted activity. 6 – 9 The rate of falling rises after the age of 70 years. 1 , 2 , 4 Several factors — such as postural hypotension, the use of multiple medications, and impairments in cognition, vision, balance, gait, and strength — increase the risk of falling and fall injuries. 1 , 2 , 4 , 5 Risk increases as the number . . .